Fertility analysis of intraspecific hybrids in Vitis vinifera and screening of superior hybrid combinations - Wang, Zhi-Lei; Yao, Fei; Hui, Miao; Wu, Dong; Wang, Ying; Han, Xing; Cao, Xiao; Li, Yi-Han; Li, Hua; Wang, Hua (Frontiers in Plant Science, 2022)
The correlations were explored between fertility indicators of intraspecific V. vinifera hybrids and different cultivars were subjected to selfing or used in reciprocal crosses by testing them as female parents or male parents. Two cold-resistant and four high-quality cultivars were selected, and the offspring of fourteen crosses and six self-combinations were evaluated. The pollen viability of the six cultivars was determined by TTC staining. Compatibility and the rates of fruit-setting, seediness, germination, emergence, and seedling were measured as parameters that can affect fertility of both hybridization and self-crossing processes. Using principal component analysis, the six fertility indexes were transformed into comprehensive principal components, and the weights of the indexes were determined. Combined with the membership function method, the fertility index was comprehensively evaluated for different crosses to screen for hybrid combinations with higher fertility. The results showed a high positive correlation between the pollen viability of the cultivar subjected to selfing and the fruit-setting rate, seediness rate, and hybrid compatibility index of the cultivar used as the male parent for crossing. Additionally, there was a one-to-one positive correlation between the fruit-setting rate, germination rate, emergence rate, and seedling rate of the selfed cultivar and the fruit-setting rate, germination rate, and seedling rate of the cultivar used as the female parent for crossing. There was some variation in the comprehensive fertility index values for the parents and combinations in different years. The comprehensive fertility index was always the highest for Ecolly as the male parent. The composite fertility index values were relatively high when Dunkelfelder, Cabernet Sauvignon, or Marselan were used as the female parent. The combinations of C1 (Cabernet Sauvignon × Ecolly), C3 (Marselan × Ecolly) and C6 (Dunkelfelder × Ecolly) exhibited relatively high comprehensive fertility indices, and pedigree clustering shows that these three combinations cluster into one class of highly fertile hybrid combinations. This study provides the basis for effective intraspecific hybrid breeding of grape (V. vinifera).